Analysis sustainability status of laeya river management for raw water supply in South Konawe Regency Southeast Sulawesi Province - Ridwan Adi Surya; Darwin Ismail; Asramid Yasin; La Aba; La Ode Muhammad Erif (Depik, 2023)
South Konawe Regency experienced a decrease in water supply and an increase in water demand, due the changes in land use caused by ongoing land exploitation, which increases runoff and decreases infiltration capacity. As a result, more water is lost to the ocean, threatening the water supply from Laeya River. Laeya River raw water is not only utilized for PDAM raw water sources, but also used to meet the domestic needs of the community, agricultural irrigation and plantations, so it is important to know the its sustainability status. This research aims to carrying out activities that control the water quality of the Laeya River, as well as to serve an information regarding the status model for the sustainability of raw water management, and to raise environmental awareness. This study was carried out in the Laeya River, South Konawe Regency. Sampling was conducted at three stations representing the upstream area of the Laeya River, the middle area and the downstream area. The Multi Dimensional Scaling (MDS) analysis method was used to conduct an analysis of the status of sustainable natural resource management for sustainable raw water supply. Based on the results can be concluded that Analysis of the 41 attributes derived from five dimensions resulted in 12 attributes acting as leverage factors in each dimension partially. To improve the sustainability status of raw water management in the research area, it is necessary to intervene the 12 attributes, namely 11 attributes that need to increase the intensity of their activities, and one attribute needs to be controlled and planned for its development properly. The results of the assessment of 41 attributes from five dimensionsin the management of the Laeya River for raw water supply in South Konawe Regency, currently is at less Sustainability status(Sustainability Index value of 36.63).KeywordsSustainability Raw WaterMDSMonte CarloRAPS-LaeyaSouth Konawe Regency